Trust in E-services technologies, practices and challenges - Song, Ronggong; Korba, Larry; Yee, George (Gale virtual reference library, 2007)
Provides an overall view of trust for e-services including definitions, constructs, and relationships with other research topics such as security, privacy, reputation and risk. Offers contributions from real-life experience and practice on how to build a trust environment for e-government services.